The "End" And Its Relationship With "Beginning" In the Arts of Novels "Aveen and Shwat" Novels as an Example - Omer, Payman M.; Mohammed, Fouad R. (Humanities Journal of University of Zakho, 2017)
This study is an attempt to clarify the essence of the "End" and its relationship with "Beginning" in the arts of novels. This is a subject that is cared and given an importance by modern literary critical discourse, particularly novel criticism; because the position of both components is strategic. The position of the "Beginning" transfers the reader from the Logic and real world into an imaginative and fictional one. In contrast to the "End", where it transfers the reader from the novel world to the real world. The beginning is a question and the answer can be found at the end of the text. Along with this concept, it has played a great role in the way of treating Kurdish Novelist in the art of the novel's text. After that, it is inquired practically about the "End" itself and its relationship with the "Beginning" of the novels (Aveen and Shwat).